Curative procedures of oral health and structural characteristics of primary dental care - Alexandre Baumgarten; Fernando Neves Hugo; Alexandre Fávero Bulgarelli; Juliana Balbinot Hilgert (Universidade de São Paulo, 2018)
ABSTRACT OBJECTIVE To evaluate if the provision of clinical dental care, by means of the main curative procedures recommended in Primary Health Care, is associated with team structural characteristics, considering the presence of a minimum set of equipment, instrument, and supplies in Brazil's primary health care services. METHODS A cross-sectional exploratory study based on data collected from 18,114 primary healthcare services with dental health teams in Brazil, in 2014. The outcome was created from the confirmation of five clinical procedures performed by the dentist, accounting for the presence of minimum equipment, instrument, and supplies to carry them out. Covariables were related to structural characteristics. Poisson regression with robust variance was used to obtain crude and adjusted prevalence ratios, with 95% confidence intervals. RESULTS A total of 1,190 (6.5%) dental health teams did not present the minimum equipment to provide clinical dental care and only 2,498 (14.8%) had all the instrument and supplies needed and provided the five curative procedures assessed. There was a positive association between the outcome and the composition of dental health teams, higher workload, performing analysis of health condition, and monitoring of oral health indicators. Additionally, the dental health teams that planned and programmed oral health actions with the primary care team monthly provided the procedures more frequently. Dentists with better employment status, career plans, graduation in public health or those who underwent permanent education activities provided the procedures more frequently. CONCLUSIONS A relevant number of Primary Health Care services did not have the infrastructure to provide clinical dental care. However, better results were found in dental health teams with oral health technicians, with higher workload and that plan their activities, as well as in those that employed dentists with better working relationships, who had dentists with degrees in public health and who underwent permanent education activities.